Acceptability and appropriateness of a clinical pathway for managing anxiety and depression in cancer patients: a mixed methods study of staff perspectives - Phyllis Butow; Heather L. Shepherd; Jessica Cuddy; Marnie Harris; Sharon He; Lindy Masya; Mona Faris; Nicole M. Rankin; Philip Beale; Afaf Girgis; Brian Kelly; Peter Grimison; et al. (BMC, 2021)
Abstract Background Clinical pathways (CPs) can improve health outcomes, but to be sustainable, must be deemed acceptable and appropriate by staff. A CP for screening and management of anxiety and depression in cancer patients (the ADAPT CP) was implemented in 12 Australian oncology services for 12 months, within a cluster randomised controlled trial of core versus enhanced implementation strategies. This paper compares staff-perceived acceptability and appropriateness of the ADAPT CP across study arms. Methods Multi-disciplinary lead teams at each service tailored, planned, championed and implemented the CP. Staff at participating services, purposively selected for diversity, completed a survey and participated in an interview prior to implementation (T0), and at midpoint (6 months: T1) and end (12 months: T2) of implementation. Interviews were recorded, transcribed and thematically analysed. Results Seven metropolitan and 5 regional services participated. Questionnaires were completed by 106, 58 and 57 staff at T0, T1 and T2 respectively. Eighty-eight staff consented to be interviewed at T0, with 89 and 76 at T1 and T2 (response rates 70%, 66% and 57%, respectively). Acceptability/appropriateness, on the quantitative measure, was high at T0 (mean of 31/35) and remained at that level throughout the study, with no differences between staff from core versus enhanced services. Perceived burden was relatively low (mean of 11/20) with no change over time. Lowest scores and greatest variability pertained to perceived impact on workload, time and cost. Four major themes were identified: 1) Mental health is an important issue which ADAPT addresses; 2) ADAPT helps staff deliver best care, and reduces staff stress; 3) ADAPT is fit for purpose, for both cancer care services and patients; 4) ADAPT: a catalyst for change. Opposing viewpoints are outlined. Conclusions This study demonstrated high staff-perceived acceptability and appropriateness of the ADAPT CP with regards to its focus, evidence-base, utility to staff and patients, and ability to create change. However, concerns remained regarding burden on staff and time commitment. Strategies from a policy and managerial level will likely be required to overcome the latter issues. Trial registration The study was registered prospectively with the ANZCTR on 22/3/2017. Trial ID ACTRN12617000411347. https://www.anzctr.org.au/ .